PET Imaging of FSHR Expression in Tumors with 68Ga-Labeled FSH1 Peptide. (23rd August 2017) - Pan, Donghui; Liu, Guifeng; Xu, Yuping; Wang, Yanting; Yue, Yuanyuan; Wang, Lizhen; Yan, Junjie; Wang, Xinyu; Yang, Runlin; Yang, Min
Abstract : FSHR is an appealing target for cancer theranostics. Radiolabeled FSH1 and its derivatives have shown potential to in vivo detect FSHR expression. However, moderate labeling yields ( 50% nondecay-corrected) may partially limit their wide use. 68 Ga is an excellent PET nuclide due to availability, nearly quantitative reaction, and short physical half-life. In this study, 68 Ga labeled FSH1 peptide was developed for imaging of FSHR in cancers. In vitro studies and MicroPET imaging were performed in PC-3 prostate tumor model. [ 68 Ga] Ga-NOTA-MAL-FSH1 can be produced within 20 min with 93.2 ± 2.1 % yield and the radiochemical purity was greater than 95%. It showed that [ 68 Ga] Ga-NOTA-MAL-FSH1 possessed FSHR binding affinities. The tracer was stable in PBS and human serum for at least 2 hours. MicroPET imaging revealed that the PC-3 xenografts were clearly visualized and the tumor uptakes were 1 . 87 ± 0.10, 1.26 ± 0.06, and 0.71 ± 0.10 % ID/g at 0.5, 1 h, and 2 h postinjection. The corresponding tumor to blood and tumor to muscle ratios were 1.77 ± 0.70, 7.94 ± 1.35, and 10.37 ± 1.16 and 7.42 ± 0.46, 26.13 ± 2.99, and 36.40 ± 2.54, respectively. FSHR binding specificity was also demonstrated by reduced tumor uptake of [ 68 Ga] Ga-NOTA-MAL-FSH1 after coinjecting excess unlabeled FSH1 peptide. The favorable characters of [ 68 Ga] Ga-NOTA-MAL-FSH1 such as convenient synthesis and specific tumor uptake warrant its further investigation for FSHR expression imaging.